2019
DOI: 10.1088/1361-6463/ab05a0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of vacuum flashover on surface roughness

Abstract: An investigation is conducted regarding the influence of surface roughness on the flashover strength of an insulator in vacuum. A series of experiments is first presented, showing the relationship between surface roughness and flashover voltage, combined with measurement of surface potential distribution. It is found that surface charging on a roughened dielectric is suppressed remarkably; also the flashover voltage threshold depicts a rise-and-fall trend with roughness increasing, exhibiting a voltage summit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 54 publications
1
54
0
Order By: Relevance
“…Similar studies have also been conducted by Song et al [22]. Surface roughness has been studied systematically by Guo et al [14], it is shown that both SEE and the surface charge accumulation are remarkably inhibited on a roughened surface. While for the flashover voltage, a rise‐and‐fall trend is observed as the increase of the surface roughness and there is a peak at a certain roughness value.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar studies have also been conducted by Song et al [22]. Surface roughness has been studied systematically by Guo et al [14], it is shown that both SEE and the surface charge accumulation are remarkably inhibited on a roughened surface. While for the flashover voltage, a rise‐and‐fall trend is observed as the increase of the surface roughness and there is a peak at a certain roughness value.…”
Section: Introductionsupporting
confidence: 68%
“…It has been known that the surface treatment, like surface roughness, fluorination and grooves, can significantly affect the formation of the surface discharge [14][15][16]. The multipactor and charging behaviours on a plain surface have been recently studied by Sun et al [17] showing that the secondary emission yield (SEY) curve of the material has a remarkable impact on the average charge density and the flashover voltage.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in roughness causes electrons to be directly emitted on the insulator surface rather than to collide with the surface to excite secondary electrons. This phenomenon results in a decrease in the secondary electron emission coefficient, finally, an increase in the surface flashover voltage [64]. Besides, using HF to coat the metal and its oxides on insulator can reduce surface resistance and the accumulation of surface charges, so that the surface flashover voltage in vacuum can be increased [65].…”
Section: Surface Modificationmentioning
confidence: 99%
“…Generally, surface modification methods include sanding, coating, fluorination or oxidation, electron beam irradiation, plasma treatments and so on. For the effect of surface roughness on surface flashover in vacuum [59–64], studies show that the surface flashover voltage increases along with the increase of roughness. The charge density on the material surface decrease significantly as the roughness increase, but the surface flashover voltage is increased [61, 62].…”
Section: Materials Modificationmentioning
confidence: 99%
“…Previous studies have shown that Ra less than 1 μm has no significant effect on flashover process. [32,33] Therefore, the influence of roughness on flashover can be ignored in this sample. Figure 11 shows the distribution of sample surface potential after 90 seconds charging.…”
Section: Surface Roughnessmentioning
confidence: 99%